2003
DOI: 10.1099/jmm.0.05210-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in phage-typing patterns in vancomycin-intermediate Staphylococcus aureus

Abstract: The ability of phage-typing and SmaI chromosomal RFLPs to conclude appropriate strain relatedness between a collection of 12 well-characterized in vitro-selected vancomycinintermediate Staphylococcus aureus (VISA) strains and their seven vancomycin-susceptible parent strains is reported. Generally, no SmaI RFLP alterations were observed in VISA strains when they were compared with their respective parent strains, and clonal relationships between isogenic strains were clearly evident. Unlike the SmaI RFLP resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Both strains showed a strong reduction in phage susceptibility. A contrast in phage typeability in isogenic VISA/VSSA pairs was also observed by Gustafson et al ( 39 ). In our study, the reason for the absence of phage typeability of S. aureus VC40 was the difference in the glycosylation pattern of the WTA.…”
Section: Discussionsupporting
confidence: 67%
“…Both strains showed a strong reduction in phage susceptibility. A contrast in phage typeability in isogenic VISA/VSSA pairs was also observed by Gustafson et al ( 39 ). In our study, the reason for the absence of phage typeability of S. aureus VC40 was the difference in the glycosylation pattern of the WTA.…”
Section: Discussionsupporting
confidence: 67%
“…SmaI chromosomal restriction fragment length pulsed-field gel electrophoresis studies have confirmed the close relationship between the parent and GISA strains within each set of strains (17). However, some loss of phage typeability was noted in GISA strains compared to that of their parent strains.…”
mentioning
confidence: 72%
“…Teichoic acid comprises part of the S. aureus phage receptor site (7). Gustafson et al (17) have reported a decrease in the number of phage types to which the BB270, 13136 p Ϫ m ϩ , and COL GISA strains were susceptible compared to the numbers for their parent strains. This might involve decreased wall teichoic acid levels and the severe autolytic deficiency in the GISA strains (see below), which may interfere with phage lysis.…”
Section: Discussionmentioning
confidence: 99%
“…The unrelated laboratory-derived isogenic VISA and parent strain sets have been described previously [20,33]. Laboratory VISA were derived from BB270 (a heterogeneous MRSA transductant) [34], COL (a homogenous MRSA) [35] and strain 13136p−m+, which is one of the first MRSA strains described [36].…”
Section: Methodsmentioning
confidence: 99%